2021
DOI: 10.1186/s13098-021-00710-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and the risk of insulin-requiring gestational diabetes

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases; however, there has been little research into its impact on gestational diabetes mellitus (GDM). Methods This study included 308,095 women registered in the Korean National Health Insurance Service database, who delivered between 2011 and 2015 and received a health examination within 52 weeks before pregnancy. Insulin-requiring GDM was defined as no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Moreover, a stronger correlation was found in the cohort of women without metabolic syndrome before pregnancy. This confirms the hypothesis that NAFLD is an independent risk factor for CKD, regardless of the presence or absence of metabolic syndrome [35].…”
Section: Aimsupporting
confidence: 87%
“…Moreover, a stronger correlation was found in the cohort of women without metabolic syndrome before pregnancy. This confirms the hypothesis that NAFLD is an independent risk factor for CKD, regardless of the presence or absence of metabolic syndrome [35].…”
Section: Aimsupporting
confidence: 87%
“…It has been observed that pregnancy, despite being a physiological moment in a woman's life, can evoke early symptoms of future pathologies such as NAFLD. Several studies, based on the correlation of events occurring in pregnancy and the manifestation of NAFLD over time, have shown an association between some conditions, such as gestational diabetes mellitus (GDM) or eclampsia, and NAFLD in older women [68]. This correlation is confirmed in the study conducted by Hagstrom et al, which considers a A variety of foods contain choline, with meat, fish, nuts, dairy products and eggs providing the richest sources.…”
Section: Pregnancy and Breast Feeding Are Alarm Bells For Nafld In Pr...mentioning
confidence: 81%
“…In a large cohort study, NAFLD was detected as a significant risk factor for developing insulin-requiring GDM. Females with NAFLD had a higher likelihood of requiring insulin for GDM (OR=4.19; 95% CI 3.37-5.23), with risk increasing across fatty liver index categories [10].…”
Section: Discussionmentioning
confidence: 99%